2018
DOI: 10.1007/s00442-018-4217-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional plasticity in vertebrate scavenger assemblages in the presence of introduced competitors

Abstract: Introduced species may suppress or enhance ecological functions, or they may have neutral effects in ecosystems where they replace or complement native species. Few studies, however, have explicitly tested for these trajectories, and for the effect these might have for native species. In this study, we experimentally test the trajectory and scale of change in the function of 'carrion removal' at different carrion loads along ocean beaches in Eastern Australia that have different numbers of introduced red foxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…It has, however, also been suggested that low redundancy and high complementarity can characterize animal assemblages and ecological functions on coral reefs (Brandl & Bellwood, ; D'agata et al, ), in kelp forests (Ling, Johnson, Frusher, & Ridgway, ; Micheli & Halpern, ) and over seagrass meadows (Duffy et al, ; Reynolds et al, ), where herbivory and piscivory are frequently performed by a small suite of species (Bellwood et al, ; Duffy et al, ; Martin et al, ). New research suggests that low redundancy and high complementarity might also be features of animal assemblages in estuaries, coastal bays and on ocean beaches (Bingham et al, ; Gilby, Tibbetts, & Stevens, ; Olds, Frohloff, et al, ). It is not clear, however, whether these are prominent, and widespread attributes of coastal food webs, or how functional niche space changes in response to habitat transformation, heavy harvesting pressure or pollution.…”
Section: Introductionmentioning
confidence: 99%
“…It has, however, also been suggested that low redundancy and high complementarity can characterize animal assemblages and ecological functions on coral reefs (Brandl & Bellwood, ; D'agata et al, ), in kelp forests (Ling, Johnson, Frusher, & Ridgway, ; Micheli & Halpern, ) and over seagrass meadows (Duffy et al, ; Reynolds et al, ), where herbivory and piscivory are frequently performed by a small suite of species (Bellwood et al, ; Duffy et al, ; Martin et al, ). New research suggests that low redundancy and high complementarity might also be features of animal assemblages in estuaries, coastal bays and on ocean beaches (Bingham et al, ; Gilby, Tibbetts, & Stevens, ; Olds, Frohloff, et al, ). It is not clear, however, whether these are prominent, and widespread attributes of coastal food webs, or how functional niche space changes in response to habitat transformation, heavy harvesting pressure or pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, functional replacement in urban habitats is likely not the outcome of the numerical replacement of scavenger individuals. Second, domestic pet depression (Bingham et al 2018;Cunningham et al 2018): introduced domestic pets suppress the activity of native scavenger species and the reduced consumption is replaced by their own scavenging. Our results support a functional replacement by a behavioural change of native facultative scavengers due to the presences of the introduced species.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of facultative scavengers might be an important general phenomenon since a high proportion of the animals on the Worst Invasive Species list are facultative scavengers (Lowe et al 2000;Wilson & Wolkovich 2011). However, introduced facultative scavenger species may not cause a decline in carrion decomposition rates: they can also replace or augment the ecological function of native species (Didham et al 2005;Schlaepfer, Sax & Olden 2011;Bingham et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For mammals, many terrestrial species occasionally forage on living macrophytes or invertebrates in the lower intertidal zone at low tide (Carlton & Hodder, 2003). Populations of the coyote (Rose & Polis, 1998) and foxes (Cypher et al, 2014;Bingham et al, 2018;Schlacher et al, 2020) have been linked directly to either marine-derived carrion or wrack-associated invertebrates as food sources (Table 5). In comparison, deer species have been observed foraging directly on beach-cast macroalgae (Conradt, 2000;Hansen et al, 2019).…”
Section: (C) Birds Mammals and Reptilesmentioning
confidence: 99%
“…are widespread consumers of birds, fish, mammals, amphibians, eggs, and insects, and carrion can at times dominate their diet (Guarino, 2001). Indeed, lace monitors regularly consume fish carcasses (Schlacher et al, 2013b;Bingham et al, 2018). Similarly, in the USA, cottonmouth snakes (Agkistrodon piscivorus conanti) traverse areas of vegetation at the beach's edge and feed on fish that have been discarded, or regurgitated, by colonial waterbirds (Lillywhite et al, 2008).…”
Section: (E) Scavengingmentioning
confidence: 99%